Acute Diarrheal Outbreak in 2022 Karachi, Pakistan: To Determine its Clinical Spectrum, Risk Factors and Complications - Abbasi, Amanullah; Tahir, Syeda Anjala; Ali Asghar, Sarrah; Huang, Helen; Rahim, Kanza; Upadhyaya, Ashutosh (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: To identify the possible source of the outbreak and risk factors and suggest evidence-based recommendations for prevention and disease control in Pakistan. Methodology: This cross-sectional study was conducted in Civil Hospital Karachi, Pakistan, from March to May 2022. A total of 90 patients with a history of more than one watery stool in 24 hours were included in the study. The data about demographics, hygienic practices, illness characteristics, treatment, and biochemical parameters, including serum electrolytes and creatinine levels, were recorded. IBM SPSS version 26 was used for data analysis. Results: The majority (83.3%) of symptoms were for less than one week. The mean family size was 6.7, SD 3.2, and 73.3% of patients had low income. Un-filtered municipal pipelines were the primary source of drinking water for 85.6% of patients, and 82.2% drank from tap water. Diarrhea (100%) and vomiting (81.1%), followed by abdominal discomfort (53.3%), were the most common symptoms, and 19 patients suffered acute kidney injury that resulted in the need for dialysis for a short time. Among 91 cases, only seven stool samples were positive for Vibrio cholera. Conclusions: The study suggests the contaminated drinking water as a source of the outbreak, with independent risk factors such as large family size and low income. V. Cholera was indicated as the causative pathogen but with a low positivity rate; it may be due to the presence of uncommon serotype or a mutant variant of vibrio cholera for the outbreak.